Evaluation of oxidative stress on Zebrafish under different pH and dissolved oxygen levels using MDA as biomarker: Oxidative stress in Zebrafish - Chowdhury, Sabarna; Saikia, Surjya (Aquaculture Department, University of Mataram, 2023)
Oxidative stress on zebrafish (Danio rerio) has been evaluated for pH (four levels namely pH 4.5-5.5, 5.5-6.5, 7.5-8.5 and 8.5-9.5) and Dissolved Oxygen (DO 20-30%, 40-50% and 60-70%) in terms of oxygen saturation. Temporally, the exposure for pH levels were maintained from as 1h, 2h, 3h and 4h and for DO, it was (4h, 8h, 12h and 16h. The malondialdehyde (MDA) was used as biomarker of oxidative stress. It was observed that out of all tissues (skeletal muscle, liver, gill and brain) analyzed, zebrafish showed highest stress response in skeletal muscle against both environmental ambiances. In case of pH levels, significant increase in MDA level in skeletal muscle was recorded at pH 4.5-5.5, and the MDA level of skeletal muscle at 2h showed significant increase at this level of pH. Whereas, at DO 20-30% saturation level, skeletal muscle tissue significantly responded at this level of DO saturation and showed the maximum MDA level compared to the other tissues. On analysis for the duration of exposure, it was observed that skeletal muscle of zebrafish showed highest levels of MDA at DO 40-50% O2 saturation for 12h. In conclusion, it has become evident that zebrafish may undergo oxidative stress at pH 4.5-5.5 when exposed for 2hours, similarly, for DO it is 20-30% saturation for 12 hour exposure.